The critical and specific transcriptional regulator of the microenvironmental niche for hematopoietic stem and progenitor cells - Omatsu, Yoshiki; Nagasawa, Takashi (Current opinion in hematology, 2015)
It has been assumed that the special microenvironments known as niches in the marrow play an essential role in maintaining hematopoietic stem and progenitor cells (HSPCs), and the identity of the HSPC niche has been a subject of long-standing debate. Recent studies identified cells, which create microenvironments meeting the criteria for HSPC niches and the critical transcriptional regulators of their development and maintenance. Osterix as well as Ebf2 and Bmi1 are critical but not specific transcriptional regulators of HSPC niche development. The transcription factor Foxc1 is expressed preferentially in a population of adipo-osteogenic progenitors, termed CXCL12-abundant reticular (CAR) cells, which create HSPC niches and are largely equivalent to stem cell factor and Lepr-expressing cells, in developing and adult bone marrow. Foxc1 is essential for CAR cell development and maintenance of bone marrow niches for HSPCs upregulating CXCL12 and SCF expression and inhibition of adipogenic processes in CAR cell progenitors. Foxc1 is the first critical and specific transcriptional regulator that is required for development and maintenance of cells creating HSPC niches, including a specialized population of adipo-osteogenic progenitors in bone marrow.